Stock Valuation With Multiples: Price Earning Ratio (Per) And Price To Book Value (Pbv) 2024 (Case Study On Banking Sub-Sector Stocks On The Indonesia Stock Exchange 2020-2024) - Najoan, Robert J.S (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to determine the intrinsic value of stocks and stock positions of companies in the banking sub-sector using the assessment of price earning ratio (PER) and price book value (PBV) for the period 2020-2024. This research is a type of descriptive quantitative analysis research where the research variables used are Price Earning Ratio (PER) and Price to Book Value (PBV) in issuers of the banking sub-sector listed on the Indonesia Stock Exchange for the period of 2020-2024. The population in this study is 47 companies in the banking sub-sector listed on the Indonesia Stock Exchange. The sampling technique is with the purposive sampling method which produces 5 issuers as samples, namely PT Bank Central Asia, PT Bank Negara Indonesia, PT Bank Rakyat Indonesia, PT Bank Tabungan Negara, and PT Bank Mandiri. The data source used is secondary data with literature study and documentation collection techniques. The analysis used is a multiple equity method with a PBV and PER ratio approach. The results of this study show that based on the PER approach, there are 2 (two) issuers, namely PT Bank Central Asia (BBCA) and PT Bank Tabungan Negara (BBTN) whose share prices are overvalued and 3 (three) issuers, namely PT Bank Negara Indonesia (BBNI), PT Bank Rakyat Indonesia (BBRI) and PT Bank Mandiri (BMRI) whose share prices are overvalued. Meanwhile, based on the PBV approach, there are 3 (three) issuers whose share prices are overvalued, namely PT Bank Central Asia (BBCA), PT Bank Rakyat Indonesia (BBRI) and PT Bank Mandiri (BMRI) and 2 (two) issuers whose share prices are undervalued, namely PT Bank Negara Indonesia (BBNI) and PT Bank Tabungan Negara (BBTN).